What could Paul have meant by ‘against nature’ (παρὰ φύσιν) as written in Romans 1:26? Striving for the well-being and health of all people - Andries G. van Aarde (HTS Teologiese Studies/Theological Studies, 2021)
The point of departure of this article is postmodern philosopher Michel Foucault’s ‘archaeological analysis’ of the history of sexuality, seen from the lens of the South African philosopher Johann Beukes. Foucault points out that since the circulation of the so-called handbooks on penance in the 6th century CE, same-gender sex was seen as a punishable sin. With regard to perspectives before this period, Foucault reflects specifically on the contribution of the Christian theologian Augustine (354–430 CE), and particularly Augustine’s interpretation of the Greek expression para phusin (παρὰ φύσιν) as ‘against nature’ as written in Paul’s letter to the Romans (1:26). He argues that this interpretation by Augustine represents a trend in contemporaneous thinking of non-Christian writers such as Plutarch and Themistios. The aim of this article is to demonstrate that a much more influential stimulus from another non-Christian thinker, namely Artemidorus of Daldis (2nd century CE), created a common context that influenced Augustine’s views and subsequently those on same-gender sex, sexual identity, and heterosexual marriage within the Christian tradition.